Time-resolved botulinum neurotoxin A activity monitored using peptide-functionalized Au nanoparticle energy transfer sensors - Wang, Yi (2015)
We report herein on the employment of synthetic peptide-functionalized gold nanoparticles (AuNPs) with various diameters as radiative quenchers for the time-resolved monitoring of botulinum A light chain (BoLcA) activity. The results demonstrate that larger AuNPs provide higher energy transfer efficiencies between the dye and the AuNPs, but poorer BoLcA activities for the proteolysis of peptides because of steric constraints. The initial turnover number for the BoLcA proteolysis of peptides on 18 nm AuNPs was retarded by a factor of 80 as compared with 1.4 nm AuNPs. A similar phenomenon has been observed for trypsin, however, with less hindrance on large AuNPs. Thus, the use of smaller 1.4 nm AuNPs in conjunction with robust synthetic peptides provides an attractive format for the time-resolved monitoring of protease activity and for BoLcA sensing at a highly competitive limit of detection (1 pM).